Expression of Non-visual Opsins Opn3 and Opn5 in the Developing Inner Retinal Cells of Birds. Light-Responses in Müller Glial Cells - Rios, Maximiliano N.; Marchese, Natalia A.; Guido, Mario E. (Frontiers in Cellular Neuroscience, 2019)
The avian retina is composed of different types of photoreceptors responsible for image and non-image forming tasks: the visual photoreceptor cells (cones and rods), the melanopsin-expressing intrinsically photoresponsive retinal ganglion cells (ipRGCs) and horizontal cells. Furthermore, the nonvisual opsins Opn3 (encephalopsin/panaopsin) and Opn5 (neuropsin) have been shown to be expressed in the vertebrate inner retina, responding to blue (BL) and UV light, respectively. Here we investigated the expression and localization of Opn3 and Opn5 in the developing chick retina at different embryonic days (E) as well as in primary cultures of retinal Müller glial cells (MC). Opn3 and Opn5 mRNAs and proteins appeared as early as E10 although traces of Opn3- and Opn5-like proteins were seen earlier by E7 in the forming RGC layer and in glial cells extending throughout the developing nuclear layer. Later on, at postnatal days 1-10 (PN1-10) a significant expression of Opn3 was observed in inner retinal cells and processes in plexiform layers, together with expression of the glial markers glutamine synthetase (GS) and the glial fibrillary acidic protein (GFAP). Opn3 and Opn5 were found to be expressed in primary MC cultures prepared at E8 and kept for two weeks. In addition, significant effects of BL exposure on Opn3 expression and subcellular localization were observed in MCs as BL significantly increased its levels and modified its nuclear location when compared with dark-controls, through a mechanism dependent on protein synthesis. More importantly, a subpopulation of MCs responded to brief BL pulses by increasing intracellular Ca2+ levels; whereas light-responses were completely abolished with the retinal bleacher hydroxylamine pretreatment. Taken together, our findings show that these two opsins are expressed in inner retinal cells and MCs of the chicken retina at early developmental phases and remain expressed in the mature retina at postnatal days. In addition, the novel photic responses seen in MCs may suggest another important role for the glia in retinal physiology.